Nancie L. González. Dollar, dove and eagle: one hundred years of palestinian migration to Honduras. Ann Arbor, [Michigan]: The University of Michigan Press, 1992. 228 pp. - Marín Guzmán, Roberto (Estudios de Asia y África, 1996)
-